What unites us? Urban space aesthetic communication and Agenda 2030 - Svizzero, Renata [UNESP]; Reno, Denis [UNESP] (Univ Santiago Compostela, 2020)
With the passage from a modern to a contemporary city, new questions and challenges have arisen, in which technological changes have disorganized and reorganized the territory and, to understand the consequences caused in the cities and their functioning, a sociocultural reading is required. Studies have shown the importance of dialogic relationships between the architecture of the place and the real socioeconomic and cultural needs of users. The UN Agenda 2030 proposes to improve the lives of people everywhere to ensure a life with dignity, in which one of its aims is to make cities and human settlements inclusive, safe, resilient and sustainable. This study aims to offer new parameters for the development of a look that will make possible, from a social and cultural analysis, an inclusive public space as a new way of looking at the city.
Keywords: City; communication; aesthetics; image; social inclusion